Analysis of Business Development for MSMEs In Bandung City - Nugraha Saefudin; Yenny Maya Dora; Ifa Latifah (Islamic University of Kalimantan MAB Banjarmasin, 2023)
The Indonesian state after the Covid 19 pandemic, has not yet recovered until now the role of MSMEs is very necessary. This is because the potential of MSMEs is currently very large in absorbing labor, in connection with the contribution of MSMEs, the empowerment and development of MSMEs is something that needs to be done continuously. This study aims to determine the role of product innovation, product quality and financial management on the development of MSMEs after the Covid 19 pandemic. The research was conducted on MSMEs in Bandung City. Data collection was carried out on MSMEs using a questionnaire of as many as 100 MSME players in Bandung City. The collected data were analyzed using SPSS 25.0. From the results of data processing, it is found that Product Innovation, Product Quality and Financial Management partially affect the development of MSME businesses. And together Product Innovation, Product Quality and Financial Management have an effect on Business Development. This means that to carry out business development MSMEs must always make product innovations in the products they produce while maintaining the quality of the products produced. In addition, MSMEs must also carry out structured and correct financial management.